1543 The value of safety and health to society – new global and european estimates of economic impact. (24th April 2018) - Elsler, Dietmar; Takala, Jukka; Remes, Jouko
Abstract : Introduction: Establishing a reliable and comprehensive estimate of the cost to society of all occupational accidents and work-related illnesses or acquired disabilities is a complex task. However, it is vital that policy-makers be aware of the scope and scale of poor or non OSH in order to implement effective measures in this policy area. If we do not value life and health impacts, we will implicitly make a trade-off or these values may get even assigned zero-weight. Methods: The first phase of the large-scale study commissioned by EU-OSHA in 2015, consisting of an identification and assessment of the available data relevant to costing models that is available in each of the Member States. We concluded that the development of a comprehensive, comparable estimate covering all EU member states would not be feasible at present due to the lack of data at national level. Therefore it was decided that the second phase of the project would consist of two strands. Results: First, EU-OSHA collaborated in the development of updated ILO estimates, based on available data at international level, to calculate an approximate cost estimation for each EU member state including Norway and Iceland. The findings reveal that work-related injury and illness result in the loss of 3.7% of GDP globally (EU28 3.1%), at an annual cost of roughly €2.206 billion (EU28 €446 billion) Second we commissioned research to develop a comprehensive cost estimate for five member states, where sufficient data for such a calculation is available. These results can also be used to validate and refine the ILO estimates for the European level. Discussion: The results confirm earlier research that a high level of prevention contributes to the productivity and wealth of a country. Lower prevention results in higher costs to society